Antimicrobial Resistance at the Human-Animal Interface - Murphy, Riley James Thomas (Curtin University, 2022)
Livestock-associated Methicillin-resistant Staphylococcus aureus (MRSA) are an emerging public-health issue in Australia, particularly amongst livestock and animal workers. We examined MRSA, isolated from humans and animals in Australia whole-genome sequencing and identified zoonotic and anthropozoonotic MRSA transmission, and antimicrobial-resistance gene transfer between MRSA of different host origin. This work highlights the need for expanded monitoring of microbial livestock pathogens and indicates the importance of prudent antimicrobial use in animal health.